Serum fatty acid-binding protein 3 levels differentiate active from inactive myositis and correlate with response to therapy - Latika Gupta; Sanjukta Majumder; Amita Aggarwal; Ramnath Misra; Able Lawrence (Indian Journal of Rheumatology)
Background: Delay in the diagnosis of idiopathic inflammatory myopathies (IIMs) and resultant muscle wasting leads to a setting, wherein conventional biomarkers fail to identify inflammation amid damage. Fatty acid-binding protein 3 (FABP3) has a selective location and function lending unique potential as a specific biomarker in IIM. Methods: Patients with IIM (ACR/EULAR criteria) prospectively evaluated for clinical features and laboratory data were screened to identify cases without ongoing infection, pregnancy, and renal disease. Clinical data and sera of patients and healthy controls were retrieved, and case details supplanted with standard outcome measures. For the inception cohort, 6-month follow-up sera were used for comparison of FABP3 using ELISA. Nonparametric tests were used for analysis and results expressed as median and interquartile range. Results: One hundred and thirty two IIM patients (M:F 1:3.1) of age 38 (24.5–46.0) years and 0.9 (2.3–5.1) year long disease were compared with ten healthy controls. FABP3 levels were higher in active (5.73 vs. 2.91 ng/ml, P = 0.0351) disease, more so in early IIM (n = 16, 21, 3.84 vs. 0.00 ng/ml, P = 0.002). Levels fell with treatment in responders (n = 7, 14.5–7.5 ng/dl, P = 0.03) but not in nonresponders. A serum FABP3 ≥ 4.066 had a high specificity (80.6%) to distinguish active from inactive myositis, albeit lower than conventional biomarkers. Conclusion: Serum FABP3 is elevated in active IIM, especially early disease, and decreases with treatment among responders. FABP3 has a favorable specificity but insufficient sensitivity, limiting role as a stand-alone biomarker. It might be useful in early IIM, without renal or cardiac involvement, pending further validation.